2017
DOI: 10.1212/wnl.0000000000004671
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of recurrent traumatic brain injury in the general population

Abstract: rTBI is an important contributor to the general population TBI burden. Certain risk factors can help identify individuals at higher risk of these repeated injuries. However, higher quality research that improves on rTBI surveillance methodology is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
3
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 65 publications
1
41
3
2
Order By: Relevance
“…Consistent with our results, these included prior TBI, drug use or alcohol intoxication, and comorbid psychiatric conditions. 26 Although female sex has previously been associated with an overall increased risk of stroke and venous thromboembolism in the general population, in our study, we observed that male sex was a risk factor after TBI for bleeding and recurrent TBI. [27][28][29][30][31] The present study identified alcohol use and depression as risk factors associated with recurrent TBI, similar to findings from previous studies of bleeding risk 21,32 and recurrent TBI.…”
Section: Discussioncontrasting
confidence: 49%
“…Consistent with our results, these included prior TBI, drug use or alcohol intoxication, and comorbid psychiatric conditions. 26 Although female sex has previously been associated with an overall increased risk of stroke and venous thromboembolism in the general population, in our study, we observed that male sex was a risk factor after TBI for bleeding and recurrent TBI. [27][28][29][30][31] The present study identified alcohol use and depression as risk factors associated with recurrent TBI, similar to findings from previous studies of bleeding risk 21,32 and recurrent TBI.…”
Section: Discussioncontrasting
confidence: 49%
“…Repetitive traumatic brain injury (rTBI) has been growing into a worldwide issue. In the United States, it is estimated that generally at least 5.50% of traumatic brain injury (TBI) patients experienced rTBI in the following year (Lasry et al, 2017). Compared with the general population, rTBI is more common in athletes of contact sports, including boxing and football (Mckee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recovery from TBI is a complex process and severe brain injuries commonly result in a wide range of disorders of consciousness (DOC). This condition is characterized by high heterogeneity in clinical phenotypes and, mainly, in prognostic models (Langlois et al, 2006;Menon et al, 2010;Lasry et al, 2017) that contributed to disappointing results in several clinical trials (Menon, 2009).…”
Section: Introductionmentioning
confidence: 99%